2021
DOI: 10.3390/f12040420
|View full text |Cite
|
Sign up to set email alerts
|

The Wood Quality of Small-Leaved Lime (Tilia cordata Mill.) Trees in an Urban Area: A Pilot Study

Abstract: This study performed a pilot evaluation of the wood quality—defined by a single parameter: dynamic modulus of elasticity (MOEdyn, N mm−2)—of small-leaved lime (Tilia cordata Mill.) trees in urban areas. A search of the literature revealed few studies which examined the specifics of tree wood development in urban areas. Little is known about the potential of wood from urban trees wood of their suitability for the timber industry. In this study, an acoustic velocity measuring system was used for wood quality ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Trunks of four linden trees were provided from a street in the centre of Brno, Czech Republic. It is worth mentioning that some studies showed environmental factors in urban regions can negatively impact tree growth and the wood quality of full-grown trees compared with remote regions [ 35 ]. Planks of wood were cut from the trunks, and the test specimens were made from these planks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trunks of four linden trees were provided from a street in the centre of Brno, Czech Republic. It is worth mentioning that some studies showed environmental factors in urban regions can negatively impact tree growth and the wood quality of full-grown trees compared with remote regions [ 35 ]. Planks of wood were cut from the trunks, and the test specimens were made from these planks.…”
Section: Methodsmentioning
confidence: 99%
“…Linden is usually used to manufacture boxes and crates, wood turning and furniture manufacturing [ 33 ]. Several studies have focused on the assessment of the mechanical properties of linden wood under impact loading [ 34 , 35 ] and the affecting parameters on the impact strength, such as temperature [ 36 ], or with an aim to determine them for being used as a material properties input in finite-element method (FEM) [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the small-leaved linden is an important species for urban and recreational forestry and open landscapes. These trees are often planted singly or in groups along roads and in urban parks [ 11 ]. Linden trees are distinguished by several advantages, particularly a compact leaf crown, shade tolerance, tolerance to various soil conditions, and resistance to wind and stressful urban conditions, such as smoke, dirt, dust, and air pollution [ 12 ].…”
Section: Introductionmentioning
confidence: 99%